Examination of the impact of ecological and agrotechnical factors in a maize fertilisation experiment - Becze, Zsófia (Acta Agraria Debreceniensis, 2014)
The year 2013 was rather extreme breeding year because of the uneven distribution of precipitaion and the summer heat. The experiment was set on with eight different genetic characteristics maize hybrids in 2013. In our study were included different kind of breeding season hybrids. We studied the effect of NKP fertilization and row spacing on the yield. The fertilizer doses are based on 25-year long-term experiment. Compared to control, the N40+PK treatment has also achieved a significant yield increase, although some hybrid of increasing fertilizer doses yield response to loss. The majority of hybrids reached higher yields using the 50 cm row spacing. The water release of hybrids was measured between 21th August and 17th September weekly, at the same time points. The rainy September slowed ripening hybrids and water release, so the grain wet content at harvest showed higher values.